From living lab to scalable startup: a process design methodology for innovation - Andres Garzon , Kevin (Acta Herediana, 2026)
The paper introduces the DDI (Diagnosis, Design, Implementation) framework, a novel approach to help early-stage companies integrate data-driven process design. The framework was developed using a two-layer action research methodology involving direct intervention through workshops with three German startups. It connects process design to the business model, integrates the Voice of the Customer (VOC), and is flexible with various digital tools. Quantitative analysis confirmed significant waste reduction and improved performance indicators. Qualitative analysis of participant interviews demonstrated the framework's high perceived utility. The DDI framework provides a flexible methodology for startups to build scalable, customer-centric processes, closing the critical gap between traditional optimization techniques and the needs of new ventures. The paper shows how its application strengthens university–business linkages and enhances process design capabilities in early-stage startups.